PENGARUH FAKTOR KEBIJAKAN, KINERJA PERUSAHAAN DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN - LEVINA LESMANA; MUNGNIYATI MUNGNIYATI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research was to analyze the influence of policy factors (debt policy, investment policy and dividend policy), company performance (liquidity, profitability, firm size and activity), and independent board of commissioners with firm value. Sample of this research are 93 non financial companies listed in Indonesia Stock Exchange during the research period 2013 until 2016, thus totaled 372 data. Sample selection method used was purposive sampling. Data were analyzed by using multiple regression method. In this research, firm value were measured by PBV (Price Book Value). The empirical evidence of this research indicated that debt policy, investment policy, dividend policy, profitability, and independent board of commissioner have positively effects firm’s value. Liquidity, firm size and activity have no influence on firm value.